Effect of some abiotic factors on the growth of Oreochromis niloticus Linnaeus, 1758 (Perciformes: Cichlidae) in tropical ecosystems (Cameroon) - Nchoutndignigni, Mohamed Nsangou; Kekeunou, Sévilor; Ajeagah, Gidéon; Bapfubusa, Benoit; Fomena, Abraham (Journal of Research in Biology, 2015)
The Growth of Oreochromis niloticus (2.6g initial average size) was studied in 100m2 earthen ponds for 180 days under tropical field environment. Varying fertilizing regimes consisting of Pennisetum purpureum (PP) and Musa sapientum (MS), two locally available weedy grasses were applied in duplicates in the experimental ponds, at the rate of 0.1-0.2 kg dry matter per m2 per day. Water quality parameters were monitored bimonthly between 8:00am-9:00am . Final average fish weight varied significantly (p<0.05) as follows: 43.85g, 35.5g, 59.5g, 24.9g and 50g, 2 respectively for PP, MS, MS+PP, T0 and T1. Corresponding daily growth were 2.2g/d, 0.1g/d, 0.3g/d, 0.1g/d and 0.2g/d. Survival rate equally varied significantly as follow: 60 %, 67 %, and 98 %, 70 % and 97 % respectively. During the study period, the results indicated the water quality were permissibole limits and can be used for livestock of Oreochromis niloticus.